Non‐Thermal Plasma Assisted Fabrication of Ultrathin NiCoOx Nanosheets for High‐Performance Supercapacitor. Issue 11 (19th September 2022) - Gicha, Birhanu Bayissa; Tufa, Lemma Teshome; Goddati, Mahendra; Adhikari, Samir; Gwak, Juyoung; Lee, Jaebeom
Abstract: Transition metal based layered double hydroxides (TMLDHs) are potential candidates for supercapacitors; however, their structural staking often limits their energy density, one of the major pending obstacles in the sector. Simple, fast, and safe modification strategies such as exfoliation of jammed layers into single sheets can be a viable option to overcome those challenges. This work reports fabrication of an ultrathin nanosheets from bulk TMLDHs using superficial non‐thermal Ar‐plasma exfoliation strategy. Electrochemical characterizations have confirmed that capacitive performance of pristine NiCoO x nanosheets has improved because of Ar‐plasma induced exfoliation. A remarkable of 5.7 F cm −2 areal capacitance was achieved at a current density of 5 mA cm −2 for ultrathin Ar‐NiCoO x nanosheets. The material also exhibited excellent cyclic stability with over 88 % capacitance retention after 5000 cycles. The electrode material assembled into symmetric supercapacitor device delivering an energy density of 85.9 μWh cm −2 at a power density of 500 μW cm −2 .The higher supercapacitive performance is attributed to increased electrochemical surface area and improved capability of electron and ion transport induced by Ar‐plasma exfoliation, demonstrating an opportunity for further use of TMLDHs in the energy conversion and storage sector. Abstract : Ultrathin nanosheets : Exfoliation of TMLDHs into few layers of ultrathin nanosheets using efficient and sustainable pathways enable their wider applications in the energy storage devices. Here we employed a non‐thermal Ar‐plasma exfoliation strategy to obtain a single layer of NiCoO x nanosheets with excellence supercapacitive properties owing to improvement on the accessible active site for charge storage and transport.